1998
DOI: 10.3109/09637489809089405
|View full text |Cite
|
Sign up to set email alerts
|

Quality of mechanically deboned chicken meat frankfurter incorporated with chicken skin

Abstract: Four formulations were processed into frankfurters with different ratios of mechanically deboned chicken meat (MDCM) and cooked chicken skin (CCS) i.e. 80/0, 70/10, 60/20 and 50/30. The products were evaluated for proximate composition, cholesterol content, colour; 'L' value (lightness) and 'a' value (redness), percentage of cooking loss, physical measurements (shearforce-kgf and folding test), thiobarbituric acid value (TBA) and taste panel evaluation. The increment of CCS in the frankfurters increased the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
2
9
0
6
Order By: Relevance
“…A decrease in TBARS after a certain time is commonly seen for lipid oxidation. This is in line with results obtained by Babji et al (1998) that showed similar increases in TBARS values during storage followed by declines in TBARS. The decrease could represent the breakdown of secondary products to tertiary oxidation products.…”
Section: Resultssupporting
confidence: 93%
“…A decrease in TBARS after a certain time is commonly seen for lipid oxidation. This is in line with results obtained by Babji et al (1998) that showed similar increases in TBARS values during storage followed by declines in TBARS. The decrease could represent the breakdown of secondary products to tertiary oxidation products.…”
Section: Resultssupporting
confidence: 93%
“…Babji et al, [12] and Hsu and Yu [13] have reported that there were no significant differences in the cooking loss, texture, juiciness, aroma, oiliness and overall acceptance between burgers prepared with palm fats and the conventional ones with beef fat. Besides that, Alina et al [4] reported that in chicken nuggets containing palm fat, they had harder texture compared to the control and commercial nugget samples and palm fat in the nuggets did not affect chicken flavor as perceived by consumers from the sensory evaluation scores.…”
Section: Introductionmentioning
confidence: 99%
“…homojenize edilmiştir. Bunu takiben hazırlanan karışımdan 10 -6 ya kadar desimal dilüsyonlar hazırlanarak, besi yerlerine ekimleri yapılmış, uygun sıcaklık derecelerinde inkübas-yon sonucunda değerlendirilmiştir (3,4,14). Ridascreen SET A,B,C,D,E (R-Biopharm AG, Darmstadt Germany.…”
Section: Materyal Ve Metotunclassified
“…(14) ve Yuste ve ark. (43) burgu tipi makinalardan elde edilen örneklerdeki enterobakteri sayısını sırasıyla 7.2x10 3 ve 6.4x10 2 kob/g olarak saptamışlardır.…”
Section: Tartışma Ve Sonuçunclassified